Breaking Bad News Using Role Playing: A Multimedia Instructional Activity for Teaching Medical Trainees - Michael Mintzer; Aileen Chen; Tara Conway Copper; Sara Bauder Filmalter; Matthew Markert; Tahira Mathen; Natasha Parekh; Shalu Patel; Maria van Zuilen (Association of American Medical Colleges, 2014)
Abstract Introduction Breaking bad news is a difficult communication skill; bad news is often delivered poorly. A small-group instructional session on breaking bad news has been a component of the medical student curriculum in the University of Miami Miller School of Medicine's Longitudinal Theme in Geriatrics, Pain Management and Palliative Care for many years. In order to address faculty concerns with facilitating these complex scenarios, a variety of shorter cases that progress through increasingly more difficult clinical scenarios were developed and later recorded as a multimedia module. Methods This recorded adaptation of the breaking bad news session provides a valuable learning opportunity and resource for faculty, especially those with limited experience in facilitating role-playing instructional activities. The session uses two complex clinical scenarios, each unfolding over three-parts. All the materials necessary to effectively implement the session are included. Results The session is highly regarded by students and faculty/facilitators. The evaluation data (student and faculty evaluation questionnaires included in the appendix) are included for the year the recording was made. There were 13 small groups simultaneously participating in the breaking bad news small-group sessions; only one session was recorded. The evaluations for all the sessions were comparable and highly rated. Previous and subsequent years were likewise highly rated. Discussion This work is significant as a faculty development tool for teaching and implementing role-playing as an instructional method. This curricular element can readily replace or augment an already existing small-group session on breaking bad news. Furthermore, the individual recordings used to compile the module can be used in a variety of other courses on communication, ethics, etc. This module can be useful for medical trainees; however, it can also be used by any clinician provider (e.g., physician assistants, ARNPs, nurse specialists, hospice staff, etc.) who regularly break bad news. One drawback in using shorter cases is that students have a limited opportunity to practice the structured format (Buckman's 6-step or SPIKES) for delivering bad news. Students may need to be given other opportunities in the curriculum to demonstrate their competency in using a structure format.